1990
DOI: 10.1146/annurev.ph.52.030190.000355
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Role for a Cardiac Peptide Hormone in Fish Osmoregulation

Abstract: It is clear from the extant literature that various fish groups face chronic osmoregulatory problems that depend on the surrounding salinity. Their physiologic and hormonal responses are largely those seen in the mammals, but their terrestrial descendants have lost osmoregulatory structures such as gills and rectal glands and depend primarily on renal function. A data base is now emerging that strongly suggests that a putative atriopeptin plays a role in osmoregulation in fishes. This conclusion is supported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…A N P than atria, con firms results from morphometric and biosynthetic studies on other fish species (Baranowski and Westenfelder 1989). Because we used a heterolo gous R IA , we cannot compare our data directly with other studies on fish, in which a variety of homologous and heterologous antisera was used (Baranowski and Westenfelder 1989;Evans et al 1989;Evans 1990;Broadhead et al 1992;Powell and Miller 1992;Takei et al 1992). Most likely, our antiserum recognized both A N P and VNP (Takei et al 1992).…”
Section: A C T H and Seawater Adaptationmentioning
confidence: 95%
See 1 more Smart Citation
“…A N P than atria, con firms results from morphometric and biosynthetic studies on other fish species (Baranowski and Westenfelder 1989). Because we used a heterolo gous R IA , we cannot compare our data directly with other studies on fish, in which a variety of homologous and heterologous antisera was used (Baranowski and Westenfelder 1989;Evans et al 1989;Evans 1990;Broadhead et al 1992;Powell and Miller 1992;Takei et al 1992). Most likely, our antiserum recognized both A N P and VNP (Takei et al 1992).…”
Section: A C T H and Seawater Adaptationmentioning
confidence: 95%
“…We previously demonstrated (Balm et al 1987) that the stimulation of the interrenal which occurs under those conditions concurs with 1) an increased sensitivity of the organ to ACTH and, 2) with a significant hyperplasia of the cortico tropes. Tilapia under low pH conditions benefit 45 from increased branchial active sodium and chlo ride uptake (Balm 1986 Takei and Balment (1993), using a hom olo gous R IA , demonstrated that in SW-adapted eels, plasma A N P levels were actually lower than in FWadapted eels, which conflicts with the opinion held until then that SW adaptation in teleosts was as sociated with elevations of plasma A N P levels (Evans 1990). Our present results further highlight the species differences that exist in the mechanisms of action of A N P in the control of ion homeostasis.…”
Section: A C T H and Seawater Adaptationmentioning
confidence: 98%
“…There are several studies on the osmoregulatory actions of ANP in teleost species other than eels, the results of which are not always consistent with those of eels, as summarized in a number of reviews (23,26,51,86). Plasma ANP concentration is generally higher in SW fish than in FW fish or in euryhaline fish that are in SW than in FW (25,31,77,105).…”
Section: Osmoregulatory Actions Of Anp In Fish Other Than Eelsmentioning
confidence: 99%
“…Natriuretic peptides (NPs) are a hormone family that plays a pivotal role in cardiovascular and body fluid homeostasis in vertebrates (Brenner et al 1990, Evans 1990, Farrell & Olson 2000, Loretz & Pollina 2000, Takei 2000. While the NP family consists of atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP) and C-type natriuretic peptide (CNP) in mammals and amphibians, ANP, VNP (ventricular natriuretic peptide) and CNP occur in teleost fish.…”
Section: Introductionmentioning
confidence: 99%